Meet the Expert : Scott Anthony on Pandemic Lessons Learned in Singapore - Anthony, Scott (O'Reilly Media, Inc., 2020)
Scott Anthony is quarantined in an apartment in Singapore. Luckily, the sovereign city-state and country's "future-back" approach has it well-positioned to manage this unprecedented global health crisis. Join Scott to find out what you-and the rest of the world-can learn from Singapore in these uncertain times. Recorded on April 6, 2020. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.